A 3P4SW Based UPQC to Improve Power Quality in Medium Voltage Distribution System. (August 2019) - Senthil Vadivu, U; Keshavan, B K
Abstract: The adverse effect of power quality issues on power distribution system due to power electronics based controllers has tremendously increased in the modern power system; therfore, it is highly desired to design a novel power quality conditioner with a minimum number of switches to compensate voltage and current distortions. This proposed configuration reduces switching losses and also effectively alleviates the performance of the power quality conditioner. This paper introduces a configuration of 3P4SW (Three Phase Four Switch) UPQC (Unified Power Quality Conditioner) for both shunt and series APF (Active Power Filter) which can be implemented in medium voltage power grid. The major challenge of phase balance with only four switches in UPQC is accomplished by adaptive Self-tuning PID using neuro-fuzzy logic control and adaptive reference current generation scheme. This controller improves sag and swells compensation with better angle control via shunt and series converter performance and passive components design. The efficacy of proposed topology is tested on MATLAB/Simulink software and results are compared with the existing three phase six switch configuration (3P6SW).